Quality management practices in SMEs: a comparative study between India and Namibia. Issue 5 (1st July 2019) - Chakraborty, Ayon; Mutingi, Michael; Vashishth, Abhishek
Abstract : Purpose: Small- and medium-sized enterprises (SMEs) have now become an important part of economy for not only developed nations but also for emerging economies. Irrespective of the benefits that can be derived, SMEs in emerging economies still lack the will to implement quality management (QM) practices. Using a comparative study, the purpose of this paper is to understand the status of QM practices in SMEs of emerging economies. Design/methodology/approach: A survey-based approach was adopted to understand the established QM practices in the SMEs. A survey instrument was designed by reviewing the literature on QM initiatives in SMEs. A sample of 270 SMEs across Southern India and 189 SMEs in Namibia was selected through stratified random sampling technique. Findings: The overall response rate was 19.52 percent for India and 26.46 percent for Namibia, respectively. There were similarities and differences in responses from SMEs in both countries. Similarities are in terms of limited implementation of QM practices, and also less use of tools and techniques. Reasons for not implementing include unknown to the authors, and the high cost of training. Differences emerged in the type of market (Indian SMEs catering to one major customer), CSFs and business performance indicators. It was interesting to find that management commitment and involvement do not have a major influence as CSF for SMEs in both the countries. Originality/value: The research is the first attempt in bringing a comparative study about QM practices in SMEs from developing countries. The insights will help emerging economies to develop policies for education and training, and thus facilitate implementation of QM practices in SMEs.